2022
DOI: 10.20473/jde.v7i1.34414
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Economic Growth: The Case of The United States of America

Abstract: The purpose of this article is to find long- and short-term determinants of U.S. economic growth over the period 1970-2016. By using cointegration analysis and vector error correction models, we compensated for many variables that were not previously linked together. Empirical analysis shows that consumer spending, population, domestic investment, FDI inflows, and exports are long-term sources of economic growth, but FDI outflows, military spending, taxes, and imports are not considered long-term sources of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…Conclution and Recomdation Based on the research described above, important findings can be concluded including: Investment has a positive and significant effect on economic growth, this is in line with research from (Bakari & Tiba, 2022) for The Case Of The United States Of America, (P. N. Wulandari, Badriah, & Kadarwati, 2019), (Yuliadi, 2020) dan (L. M. Wulandari & Zuhri, 2019). Regional original income for positive and significant economic growth, this result is in line with research conducted by among others (Omodero et al, 2018), (Sengaji, Sasongko, & Sakti, 2019), (Gumanti et al, 2022).…”
Section: Esupporting
confidence: 73%
“…Conclution and Recomdation Based on the research described above, important findings can be concluded including: Investment has a positive and significant effect on economic growth, this is in line with research from (Bakari & Tiba, 2022) for The Case Of The United States Of America, (P. N. Wulandari, Badriah, & Kadarwati, 2019), (Yuliadi, 2020) dan (L. M. Wulandari & Zuhri, 2019). Regional original income for positive and significant economic growth, this result is in line with research conducted by among others (Omodero et al, 2018), (Sengaji, Sasongko, & Sakti, 2019), (Gumanti et al, 2022).…”
Section: Esupporting
confidence: 73%
“…First, GDPPC is positively associated with product innovation in the regression analysis. The novel findings of current study demonstrate that economic growth is dependent on product innovation since innovations are essential for a country’s welfare and economic expansion (Bakari et al, 2020; Klein & Şener, 2022). However, the causality analysis shows one-way causality from innovation to GDP per capita because innovation stimulates economic growth.…”
Section: Resultsmentioning
confidence: 75%
“…Galindo and Méndez-Picazo (2013) and Galindo and Méndez (2014) investigate how economic growth promotes innovative product activities in developed countries. Further, Tunisia, Bakari et al (2020) observed a positive but causal association between GDP and innovation.…”
Section: Literature Review and Research Gapmentioning
confidence: 89%
“…Por economías de América del Norte, específicamente, en el caso de Estados Unidos, los estudios muestran que el crecimiento económico estadounidense ha sido notable en las últimas décadas; y, que la infraestructura física y tecnológica, la conformación de capital humano, el dinamismo del sector industrial y de servicios, la apertura económica y financiera, el gasto gubernamental, y la fortaleza de su mercado interno han incidido directamente en este comportamiento (Adedoyin et al, 2020;Bakari & Tiba, 2022;Fosu & Twumasi, 2022;Goodfriend & Mcdermott, 2021;Kirikkaleli & Ozbeser, 2022).…”
Section: Crecimiento Económico Y Contaminación Ambiental Un Marco Ref...unclassified